2020
DOI: 10.1155/2020/8039840
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Wilms’ Tumor Proliferation and Invasion by Blocking TGF-β Receptor I in the TGF-β/Smad Signaling Pathway

Abstract: Wilms’ tumor (WT) is a common embryonal tumor, and nephrogenic rests play a critical role in WT development. The transforming growth factor β (TGF-β) signaling pathway is fundamental to embryo development and cell growth and proliferation. Moreover, TGF-β contributes to WT development, but the mechanisms of disease pathogenicity are unknown. This study investigated whether the TGF-β signaling pathway was involved in WT and whether blocking TβRI receptor inhibited WT growth, proliferation, and invasion. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…This might indicate the potential action in TGFβ1 cytostatic effect in controlling cell proliferation but mediating EMT and invasion, as previously reported in WT (30,32,33). The dysregulation of TGFBβ has been linked to the initiation and progression of multiple human cancers, including WT (44).…”
Section: Discussionsupporting
confidence: 70%
“…This might indicate the potential action in TGFβ1 cytostatic effect in controlling cell proliferation but mediating EMT and invasion, as previously reported in WT (30,32,33). The dysregulation of TGFBβ has been linked to the initiation and progression of multiple human cancers, including WT (44).…”
Section: Discussionsupporting
confidence: 70%
“…Utilizing the MCODE app in Cytoscape software, five modules that might serve an important role in the development of Wilms tumor were detected. Studies have demonstrated the TGF-β/Smad signaling pathway plays a key role in Wilms tumor progression (25), while Li et al showed S1P/S1P1 signaling stimulates cell migration and invasion in the disease (26). Therefore, our KEGG and GO results suggest these signaling pathways may serve a crucial role in Wilms tumor progression.…”
mentioning
confidence: 60%
“…Gene targets of miR-130a-3p were identified using miRNA target prediction databases, and we found that TGF-βRII was a possible target gene of miR-130a-3p. Previous studies showed that the TGF-β1 signaling pathway controls cell proliferation, differentiation, organ development, etc., by combing with TGF-βRII ( Shi et al, 2020 ). First, we examined whether miR-130a-3p downregulated TGF-βRII expression by Western blot and qRT-PCR ( Figures 5A–C ).…”
Section: Resultsmentioning
confidence: 99%